Exploring the Phytochemical Constituents and Bioactivities of Ocimum sanctum (Tulsi) - Yadav, Ram Prabodh; Chaudhary, Sabnam Kumari; Sah, Shree Ram; Yadav, Jitendra Kumar (Research Journal on Multi-disciplinary Issues, 2024)
Available with full text.